Bridges :interaction between construction technology and design : report /IABSE Symposium, Leningrad, 1991 - IABSE Symposium(1991 :Leningrad, R.S.F.S.R.)
"Organized by the USSR Ministry for Transport Construction, with the USSR State Committee of Construction, with the USSR State Committee of Construction (Gosstroy of the USRR) and the Soviet Group of IABSE ; co-sponsored by Comité Euro-International du Béton, Fédération Internationale de la Précontrainte."